Self Efficacy, Conscientiousness dan Employee Engagement - Etik Darul Muslikah; Diah Sofiah; Yanto Prasetyo (Indonesian Psychological Research, 2020)
This study aims to find out the correlation between self efficacy and conscientiousness with employee engagement. The hypothesis in this study is that there is a relationship between self efficacy and conscientiousness with employee engagement. This research is included in the type of quantitative non-experimental research. This research took place in St. Hospital. Vincentius a Paulo Surabaya. As for the subjects of the study were employees or employees of all sections in the St. Hospital. Vincentius a Paulo. It is known that the population residing in the St. Vincentius a Paulo is 1255 employees. This population has the characteristics of executing-level employees and permanent employees. In determining the number of subjects, researchers used the determination of subjects according to Slovin's opinion, then determined the research subjects to be extracted data in this study as many as 95 people. The analysis shows the correlation coefficient (r) of 0.815 with a significance level (p = 0.000). The results of this study are that there is a correlation between self efficacy and conscientiousness with employee engagement, so the hypothesis submitted is accepted.